(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Cancer ranks among the primary causes of death on a global level. Natural products are crucial for both cancer therapy and treatment. Traditionally, Tridax procumbens has been used to cure wound infections. The present study investigates the isolation, identification, in-vitro antioxidant, antimicrobial, and anticancer activities of isolated polysaccharides from T. procumbens L. The polysaccharide (4-deoxy-5-α-D-Rhamnonic acid (1→2) β-D-fructofuranosyl (2→1)-β-D-fructofuranosyl (2→1)-2-D-fructofuranoside) was identified using modern NMR spectroscopic techniques. In-vitro anticancer activity was assessed against MDA-MB-249 and MCF-7 using an MTT assay. The IC50 value for polysaccharide was found to be 5.06 μg/mL against MCF-7 and that of MDA MB 249 cell lines 15.68 μg/mL. The statistical analysis indicated significance at P < 0.05. The polysaccharide showed effective antibacterial activity at MIC 15.5 µg/mL against bacteria S. aureus and P. aeruginosa, respectively. The DPPH antioxidant potential of the polysaccharide was found to be outstanding, with an IC50 value of 1.01 µg/mL. It showed statistical significance at P<0.05. Therefore, the findings reveal that polysaccharides could be used as therapeutic drugs to develop anticancer and antibacterial agents from T. procumbens L.